Reliability assessment of continuous mining technological systems - Ilias, Nicolae; Andras, Iosif; Andras, A.; Dinescu, S. (НТУ "ХПИ", 2010)
Article is devoted to the analysis of reliability of parameters of continuous system of extraction with use of various approaches with the purpose of performance of a fast estimation of general efficiency of the equipment of such industrial systems, as Monte-Carlo and stress-force of intervention.

Article is devoted to the analysis of reliability of parameters of continuous system of extraction with use of various approaches with the purpose of performance of a fast estimation of general efficiency of the equipment of such industrial systems, as Monte-Carlo and stress-force of intervention.
Оценка надежности горных технологических систем непрерывного действия
Keywords: industrial systems; intervention; stress-force; непрерывная система добычи; производственные системы; стресс-силы вмешательства